Focus on Strategic Management. - Lewis, Alfred (Business Strategy Series - Volume 9, Edition 1., 2008)
This e-book presents papers which focus on the topic of strategic management. The papers focus on strategic direction, service strategies, strategic options, organizational development and business strategies in Japan.